Solid State Viscoelastic Properties, Morphological and Melt Rheological Studies on PLA/TPU/POSS Nanocomposites. Issue 10 (3rd July 2019) - Yazdaninia, Anoosha; Jafari, Seyed Hassan; Ehsani, Morteza; Khajavi, Ramin; Khonakdar, Hossein Ali
ABSTRACT: Effects of trifluoropropyl-substituted polyhedral oligomeric Silsesquioxane (POSS), on the morphological, rheological and dynamic mechanical properties of a series of poly(lactic acid) (PLA)/thermoplastic polyurethane (TPU) blends were explored, thoroughly. Microscopic techniques including scanning electron microscope (SEM) and transmission electron microscope (TEM) utilized in conjunction with viscosity measurements to explain morphological dissimilarities between different samples. A remarkable morphological refinement was observed upon addition of POSS into the 50/50 PLA/TPU blend. This morphological change was detected by means of frequency sweep rheological experiments, where the shoulder-like plateau appears as a result of increase in the contribution from the interfacial component of elasticity in the enhancement of storage modulus. Based on the results of the dynamic time sweep small amplitude oscillatory shear (SAOS) experiments, a scaling relation was proposed to quantify the kinetics of phase separation and the associate time evolution of elasticity. It turned out that POSS particles can slow down the rate of morphological coarsening up to the 50%. Using dynamic mechanical thermal analysis (DMTA) and rheological experiments, the differences in the rate of undergoing dynamics in all the length scales, starting from segmental up to the chain level, were compared for various compositions and the discrepancies were fully described based on the dissimilarities in the entanglement densities, combinatorial effects of soft and hard segments of TPU, lubricating role of POSS particles, crystallinity, and morphological characteristics of samples. GRAPHICAL ABSTRACT: GRAPHICAL ABSTRACT